Mental Health in Schools: An Overview of Multitiered Systems of Support. (November 2020) - Marsh, Robbie J.; Mathur, Sarup R.
Mental health–related disabilities are a leading cause of health issues worldwide. Because of this, an argument can be made that schools integrate mental health services for their students to positively impact their mental health outcomes. This article outlines how multitiered systems of support (MTSS) can assist schools in providing all students with mental health services including students with disabilities. The role of school-based mental health professionals (i.e., school counselor, school psychologist, school social worker) within the MTSS framework is discussed to better assist teachers in helping their students access school-based mental health services.